Reverbero journal by Iramuteq: case study (Ágora Journal, 2022)
The historiography of the independence process has analyzed, for years, the press as essential documents for understanding political disputes and discussions. Although it remains a very rich field for new research, mainly from pamphlets, we seek, using software, to collaborate with this debate on political projects published in independence periodicals based on a case study of Reverbero from a tool computer called Iramuteq. From the results obtained and the discussion with historiography, we aim to present an alternative for this type of analysis, as well as to present new elements to the historiographical discussion that became possible from the field of Digital Humanities.
Keywords: Independence; Reverbero Brazilian journal; digital humanities